Can hepatic steatosis compromise the effect of physical exercise on body composition in obese children and adolescents? - Bruna Thamyres Ciccotti Saraiva; Paula Alves Monteiro; Claudia de Carvalho Brunholi; Marcelo Rodrigues Ribeiro dos Santos; Diego Giulliano Destro Christofaro; Ismael Forte Freitas Júnior (Universidade Federal de Santa Catarina, 2017)
Physical exercise is one of the forms of prevention and treatment of obesity and associated diseases such as hepatic steatosis. The aim of this study was to analyze whether hepatic steatosis interferes in the effect of physical exercise on the body composition of obese children and adolescents. The sample consists of 40 obese individuals, 13 children (8.17±1.33 years) and 27 adolescents (12.28±1.36 years). Total and segmental body composition was estimated by DEXA. Anthropometric measurements were performed, as well as ultrasound examination of the liver to measure intra-abdominal and subcutaneous fat, and to diagnose hepatic steatosis (HS). The intervention consisted of 20 weeks, with recreational/competitive activities being applied to children and, for adolescents, concurrent training (aerobic and resistance). The Levene's, repeated-measures ANOVA and effect size tests (ES) by Eta-Squared were performed. It was observed that, although not statistically significant, analyzing the effect size, physical activity in both children (body fat ES effect time= 0.210 and ES effect group= 0.208; fat mass ES effect group = 0.338; fat android ES effect Interaction= 0.267), and adolescents (intra-abdominal fat ES effect group = 0.230) regardless of whether or not HS was effective in reducing body fat. Therefore, exercise was effective in improving the body composition of obese children and adolescents, regardless of HS.